Performance of medicinal crops in mango (Mangifera indica) based intercropping system under dryland conditions of Jammu subtropics - GUPTA, MEENAKSHI; GUPTA, S K; GUPTA, L M (The Indian Journal of Agricultural Sciences, 2021)
Mango (Mangifera indica L.) based agroforestry system offers spatial advantage for intercropping in Indian subtropics. Mango is planted at wide spacing to accommodate the large crowns needed to support the fruit yield. Wider spacing of the trees provides the vacant space to the orchardist to grow suitable and synergistic crop (vegetables/ medicinal plants) to supplement his income. The present investigation was done to screen out the best intercrop out of the four crops, viz. ginger, turmeric, kalmegh and stevia that can be grown in old mango orchards. The experiment was laid out at Experimental Farm of Advance Centre for Horticulture Research (ACHR), Sher-e-Kashmir University of Agricultural Sciences and Technology, Udheywala, Jammu, which is located at an altitude of 327m above mean sea level, between 32073´ N latitude and 74087´ E longitude. Mango orchard selected for the study had a very dense canopy and thus the interception of light was only 30-40 percent than that in the open. The results revealed that shade had profound influence on the survival, growth and yield of ginger, turmeric, stevia and kalmegh. The higher values for plant height, number of leaves, were recorded in ginger and turmeric under shade compared to stevia and kalmegh. Stevia had a very poor survival percentage (11.99%) under mango as compared to open. Likewise ginger had a poor survival percentage (13.22%) in the open compared to that under the mango canopy. Thus, it was concluded that under the subtropical conditions of Jammu region, ginger, turmeric and kalmegh can be grown successfully as intercrops under partial shade of mango trees, however, stevia cannot be integrated. The most remunerative crop among the four, in terms of yield was turmeric followed by ginger and kalmegh.